Sustentación de caso: propuesta de un plan estratégico del ingreso al mercado peruano de una empresa del sector fast fashion - Brenner Jaramillo, Juan Gonzalo (2018)
In the last years, Peruvian consumer has had better acceptance against changing trends in fashion market and that is why they have adopted the opening of fast fashion companies in a good way in the country. Therefore, the attractiveness of our region for big businesses of fast fashion market has managed to incorporate companies as Zara, H&M, Forever 21, opening stores inside and outside the capital, considering adapting its offer and business model to Peruvian consumers characteristics. The creation of an appropiate strategic plan to transfer the know-how of the brand, attract the population and deal with the key competitors determine the success of the business in the country y its growth in the region.